The science of high performance: Insights from elite sport - Van Someren, K. (TopMedTalk, 2019)
Insights and perspectives on the science of prehabilitation from a very different angle. It's often said on TopMedTalk that preparing for an operation is not unlike getting ready for a marathon; how do the insights of professionals who work with elite sports men and women to ensure they are fully prepared to do their physical best, on the world stage? Also, what about the teamwork inherent in such activities as the pitstop of a formula one car? Athletes, coaches and a wide number of different experts come into play ensuring a multidisciplinary team converge with essentially the same end in sight as a perioperative prehabilitation team; optimum performance at a crucial time.